A kind of EVA film for acid-removing solar cell and preparation method thereof
By using composite hydrotalcite acid remover and aminated anti-PID composite filler in EVA film, the problem of aging and failure of EVA film under high temperature and humidity conditions is solved, and stronger acid removal ability and mechanical properties are achieved, and the performance of the EVA film is extended. The lifespan of solar photovoltaic modules.
Patent Information
- Application Number
- CN202411641331.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing EVA film is prone to aging and failure under high temperature and humidity conditions, resulting in a decrease in power and shortening of the life of solar photovoltaic modules. Vinyl acetate produces acetic acid in a high temperature and high humidity environment, resulting in deterioration and foaming of the film, affecting battery function. .
Acid-removing EVA film is used, and its formulation includes 86 to 95 parts of EVA resin, 1.8 to 4 parts of main crosslinking agent, 0.1 to 0.5 parts of accelerating crosslinking agent, 1.3 to 3.2 parts of aminolated anti-PID composite filler, 0.1 to 1.8 parts of Compound hydrotalcite acid remover, 0.1 to 1.5 parts of lubricant, 0.04 to 1 part of ultraviolet absorber, 0.01 to 1 part of light stabilizer, 0.1 to 1 part of antioxidant, and 0.1 to 0.5 parts of coupling agent. The acid removal ability and mechanical properties of the film are enhanced by the combination of phosphate intercalated magnesium-aluminum hydrotalcite, nanotitanium dioxide particles and aminolated anti-PID composite filler.
Effectively adsorb and neutralize the acetic acid released in the EVA film, reduce the reaction of acetic acid with the glass surface alkali, reduce the generation and migration of Na+, prevent charge accumulation and abnormal movement, significantly improve the aging resistance and PID resistance of the EVA film, and extend solar energy Lifespan of photovoltaic modules.
Smart Images

Figure CN119119905B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive films, and more particularly to an EVA film for acid-removing solar cells and a preparation method thereof. Background Art
[0002] Solar photovoltaic modules are currently the most common solar energy utilization equipment, and their performance and life are affected by the encapsulation film. As a key material for solar photovoltaic modules, EVA (ethylene-vinyl acetate copolymer) encapsulation film is widely used in solar photovoltaic modules to fix and protect solar cells due to its excellent light transmittance, weather resistance and bonding properties. Since solar photovoltaic modules are exposed to complex external environments all year round, EVA films must have good weather resistance to ensure long-term stable operation of the modules. However, there are various problems in the market, such as EVA films are prone to aging and failure under high temperature and humidity conditions, resulting in reduced power and shortened life of photovoltaic modules.
[0003] In addition, the vinyl acetate in the EVA film will produce acetic acid when exposed to high temperature and high humidity outdoor environment or process temperature conditions during module manufacturing. When acetic acid is produced, the EVA film will deteriorate and foam inside the module, thereby reducing battery function and shortening the life of the entire module. In addition, as the amount of acetic acid that moves freely in the EVA film increases, the reaction between the free-moving acetic acid and the alkali precipitated on the glass surface will also accelerate, prompting Na + The production of freely movable Na + Under the action of an external electric field, it moves to the surface of the solar cell and accumulates in the anti-reflection layer, causing the photovoltaic module to face the problem of significant power attenuation or even failure in a short period of time. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an acid-removing EVA film for solar cells and a preparation method thereof.
[0005] An acid-removing EVA film for solar cells comprises the following raw materials in parts by weight:
[0006] 86-95 parts of EVA resin, 1.8-4 parts of main cross-linking agent, 0.1-0.5 parts of auxiliary cross-linking agent, 1.3-3.2 parts of amino anti-PID composite filler, 0.1-1.8 parts of composite hydrotalcite acid scavenger, 0.1-1.5 parts of lubricant, 0.04-1 parts of ultraviolet absorber, 0.01-1 parts of light stabilizer, 0.1-1 parts of antioxidant and 0.1-0.5 parts of coupling agent;
[0007] The raw materials for preparing the composite hydrotalcite acid scavenger include: 5 to 20 parts of phosphate intercalated magnesium aluminum hydrotalcite, 1 to 14 parts of nano titanium dioxide particles, 10 to 30 parts of silane coupling agent KH-550 and 70 to 120 parts of 75% by mass ethanol solution, wherein the phosphate intercalated magnesium aluminum hydrotalcite is a layered composite material formed by inserting phosphate ions between magnesium aluminum hydrotalcite layers;
[0008] The raw materials for preparing the amination anti-PID composite filler include: 1 to 12 parts of the anti-PID composite filler, 100 to 160 parts of N, N-dimethylformamide, 20 to 45 parts of ethylenediamine and 6 to 16 parts of 30% ammonia water by mass;
[0009] The raw materials for preparing the anti-PID composite filler include: surface-modified nano-tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion, wherein the mixing mass ratio of the surface-modified nano-tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion is (1-6): (21-35): (90-130), the surface-modified nano-tin oxide is nano-tin oxide modified by a surfactant, and the mass fraction of the barium metaphosphate dispersion is 4-8%.
[0010] Furthermore, the VA content of the EVA resin is 28-33%, and the melt index is 25-43 g / 10 min.
[0011] Further, the main cross-linking agent is at least one of tert-butyl peroxycarbonate-2-ethylhexyl, tert-amyl peroxy (2-ethylhexyl) carbonate, tert-butyl peroxyacetate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate or diisopropylbenzene peroxide; the auxiliary cross-linking agent is at least one of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated neopentyl glycol diacrylate, and ethoxylated trimethylolpropane triacrylate; the lubricant is one or more of stearic acid, calcium stearate, zinc stearate, butyl stearate, stearamide, and oleamide; the ultraviolet absorber is phenyl o-hydroxybenzoate, 2-(2'- The invention discloses a novel light stabilizer comprising at least one of bis-2,2,6,6-tetramethylpiperidinol sebacate, N,N,-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine and 2,4-dichloro-6-(4-morpholinyl)-1,3,5-triazine; a coupling agent comprising at least one of silane coupling agent KH-570, silane coupling agent KH-560, silane coupling agent KH-670 and silane coupling agent KH-550; and a antioxidant comprising at least one of antioxidant 1010 and antioxidant 168.
[0012] A method for preparing an acid-removing EVA film for a solar cell comprises the following steps:
[0013] S1: Preparation of phosphate intercalated magnesium aluminum hydrotalcite, using magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and phosphate as raw materials, sodium hydroxide as a precipitant, deionized water as a solvent, preparing a solution, titrating coprecipitation, hydrothermal treatment, washing and drying to obtain phosphate intercalated magnesium aluminum hydrotalcite;
[0014] S2: Preparation of composite hydrotalcite acid scavenger: after dispersing and mixing phosphate intercalated magnesium aluminum hydrotalcite, silane coupling agent KH-550 and 75% ethanol solution by mass, nano-titanium dioxide particles were added, and the composite hydrotalcite acid scavenger was obtained after ultrasonic dispersion, centrifugal separation, washing and drying;
[0015] S3: Preparation of anti-PID composite filler: surface modification of nano-tin oxide is performed using a surfactant to obtain surface-modified nano-tin oxide, and barium metaphosphate dispersion, silane coupling agent KH-550 and surface-modified nano-tin oxide are mixed and dispersed, and then centrifuged, washed and dried to obtain an anti-PID composite filler;
[0016] S4: Amination modification of the anti-PID composite filler, wherein the anti-PID composite filler, N,N-dimethylformamide, ethylenediamine and 30% ammonia water are mixed, and the mixture is heated and stirred in a water bath, condensed and refluxed, filtered to obtain the residue, washed and dried to obtain the amination anti-PID composite filler;
[0017] S5: Preparation of EVA film for acid-removing solar cells, EVA resin, main cross-linking agent, auxiliary cross-linking agent, amino anti-PID composite filler, composite hydrotalcite acid scavenger, lubricant, ultraviolet absorber, light stabilizer, antioxidant and coupling agent are melt-blended, and then extruded, cast, cooled and formed, and rolled up to obtain the EVA film for acid-removing solar cells.
[0018] Further, step S1: preparation of phosphate intercalated magnesium aluminum hydrotalcite specifically comprises the following steps:
[0019] S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate into deionized water, stir and dissolve to form Mg 2+ The concentration is 1.5~2.5mol / L, Al 3+ Solution A with a concentration of 0.5 to 1.5 mol / L, add sodium hydroxide to deionized water, stir to dissolve, and prepare OH - Solution B with a concentration of 1.5 to 4 mol / L, add phosphate to deionized water, stir to dissolve, and prepare PO4 3- Solution C with a concentration of 0.2 to 1 mol / L;
[0020] S1.2: Pour solution C into the reactor, and slowly drop solution A and solution B into the reactor while stirring under a nitrogen atmosphere. The dropping speed of solution A and solution B is 2 mL / min. When the volume ratio of the dropped solution A and solution B to the solution C in the reactor is (1-1.2):1:1, the dropping operation is completed, and the reaction is stirred for 1-2 hours. The pH value of the mixed solution in the reactor is adjusted to 6-8 with a sodium hydroxide solution with a concentration of 1 mol / L, and the reaction is carried out at 70-80°C for 12-48 hours;
[0021] S1.3: After the treatment is completed and the mixture is cooled naturally, the obtained colloid is collected, washed with deionized water for 2 to 5 times, and then dried at 40 to 60° C. for 12 to 24 hours to obtain phosphate-intercalated magnesium aluminum hydrotalcite.
[0022] Furthermore, in step S1.1, the phosphate is sodium phosphate or potassium phosphate.
[0023] Further, step S2: preparation of composite hydrotalcite acid scavenger, specifically comprises the following steps:
[0024] S2.1: Add 5 to 20 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 10 to 30 parts by weight of silane coupling agent KH-550 to 70 to 120 parts by weight of 75% ethanol solution, and ultrasonically disperse for 20 to 30 minutes to obtain a dispersion;
[0025] S2.2: Add 1 to 14 parts by weight of nano titanium dioxide particles to the dispersion, and ultrasonically disperse at 40 to 60° C. for 20 to 30 minutes. Subsequently, centrifuge and wash with deionized water for 2 to 3 times, and dry at 70 to 80° C. for 4 to 8 hours to obtain a composite hydrotalcite acid scavenger.
[0026] Further, step S3: preparation of anti-PID composite filler specifically comprises the following steps:
[0027] S3.1: Add nano-tin oxide to deionized water, ultrasonically disperse for 5 to 10 minutes, and prepare a nano-tin oxide dispersion with a mass fraction of 2 to 5%. Add a surfactant to the nano-tin oxide dispersion, wherein the amount of the surfactant added is 1 to 3% of the mass of the nano-tin oxide dispersion, and the surfactant is hexadecyltrimethylammonium bromide. Stir magnetically for 20 to 40 minutes, and then ultrasonically disperse for 10 to 30 minutes. Then, filter, wash and dry to obtain the surface-modified nano-tin oxide.
[0028] S3.2: Add barium metaphosphate to deionized water and ultrasonically disperse for 5 to 10 minutes to prepare a barium metaphosphate dispersion with a mass fraction of 4 to 8%. Add silane coupling agent KH-550 to the barium metaphosphate dispersion and ultrasonically disperse for 20 to 40 minutes. Then, add the surface-modified nano-tin oxide, heat to 50 to 80°C, and ultrasonically disperse for 40 to 90 minutes. Then, after centrifugation, washing and drying, an anti-PID composite filler is obtained.
[0029] Furthermore, in step S3.2, the mixing mass ratio of the surface-modified nano-tin oxide, the silane coupling agent KH-550 and the barium metaphosphate dispersion is (1-6): (21-35): (90-130).
[0030] Further, step S4: amino modification of the anti-PID composite filler specifically comprises the following steps:
[0031] S4.1: Add 1 to 12 parts by weight of anti-PID composite filler to 100 to 160 parts by weight of N,N-dimethylformamide, stir evenly, then add 20 to 45 parts by weight of ethylenediamine and 6 to 16 parts by weight of 30% ammonia water, stir and mix for 40 to 60 minutes, then continue stirring in a 45 to 60°C water bath for 20 to 40 minutes, then use a reflux condenser to condense and reflux for 4 to 6 hours, and filter the mixed solution obtained after condensation and reflux to obtain the filter residue;
[0032] S4.2: The filter residue is washed with anhydrous ethanol for 3 to 5 times to remove excess ethylenediamine, and the product obtained after washing is dried at 50 to 60° C. for 6 to 12 hours to obtain an amino-anti-PID composite filler.
[0033] The present invention has the following advantages:
[0034] 1. In the present invention, by inserting phosphate ions between the layers of magnesium-aluminum hydrotalcite, not only the interlayer distance of magnesium-aluminum hydrotalcite can be increased, the ion exchange capacity of magnesium-aluminum hydrotalcite can be improved, and the charge density between the layers of magnesium-aluminum hydrotalcite can be increased, the ability of adsorbing anions can be enhanced, and the efficiency of the ion exchange process can be improved, which is beneficial to the adsorption of acetic acid released from the EVA film. At the same time, nano-titanium dioxide particles are loaded on the surface of phosphate-intercalated magnesium-aluminum hydrotalcite. The prepared composite hydrotalcite acid scavenger can effectively increase the specific surface area of phosphate-intercalated magnesium-aluminum hydrotalcite due to the loading and addition of nano-titanium dioxide particles, provide more adsorption sites, and further enhance the adsorption and capture effect of acetic acid, so that the composite hydrotalcite acid scavenger has a stronger ability to handle acetic acid, thereby achieving the purpose of effective acid reduction and acid removal;
[0035] 2. In the present invention, the anti-PID composite filler formed by loading nano-tin oxide on the surface of barium metaphosphate is added to the EVA film for acid-removing solar cells, which is beneficial to improving the mechanical properties of the EVA film for acid-removing solar cells, and the interface effect between the nano-tin oxide and the barium metaphosphate in the anti-PID composite filler is beneficial to forming a charge transfer microenvironment for capturing and releasing ions, preventing the migration and diffusion of metal ions in the glass layer, reducing the damage caused by charge accumulation, and effectively inhibiting the abnormal movement of charge carriers, which is beneficial to improving the anti-PID ability of the EVA film for acid-removing solar cells;
[0036] 3. In the present invention, by aminated modification of the anti-PID composite filler, it is beneficial to enhance the interaction between the anti-PID composite filler and the EVA resin, improve the compatibility between the anti-PID composite filler and the EVA resin, thereby further improving the mechanical properties and durability of the acid-removing EVA film for solar cells, and the amino structure on the aminated anti-PID composite filler is alkaline, which can capture and neutralize the free acetic acid in the acid-removing EVA film for solar cells into salts, thereby reducing the content of free acetic acid in the acid-removing EVA film for solar cells, further playing the role of acid reduction and acid removal, and improving the aging resistance of the acid-removing EVA film for solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The present invention is a flow chart of a method for preparing an acid-removing EVA film for a solar cell according to an embodiment of the present invention. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] A method for preparing an EVA film for an acid-removing solar cell, such as Figure 1 As shown, the specific steps include:
[0041] S1: Preparation of phosphate intercalated magnesium aluminum hydrotalcite
[0042] S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate into deionized water, stir and dissolve to form Mg 2+ The concentration is 2mol / L, Al 3+ Solution A with a concentration of 1 mol / L, add sodium hydroxide to deionized water, stir to dissolve, and prepare OH - Solution B with a concentration of 4 mol / L, add sodium phosphate to deionized water, stir and dissolve to prepare PO4 3- Solution C with a concentration of 1 mol / L;
[0043] S1.2: Pour solution C into the reactor, and slowly drop solution A and solution B into the reactor while stirring under a nitrogen atmosphere. The dropping speed of solution A and solution B is 2 mL / min. When the volume ratio of the dropped solution A and solution B to the solution C in the reactor is 1:1:1, the dropping operation is completed. Stir the reaction for 2 h, adjust the pH value of the mixed solution in the reactor to 7 with a sodium hydroxide solution with a concentration of 1 mol / L, and react at 80°C for 24 h;
[0044] S1.3: After the treatment is completed and the mixture is cooled naturally, the obtained colloid is collected, washed with deionized water for 5 times, and then dried at 50° C. for 24 h to obtain phosphate-intercalated magnesium-aluminum hydrotalcite;
[0045] S2: Preparation of composite hydrotalcite acid scavenger
[0046] S2.1: 20 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 30 parts by weight of silane coupling agent KH-550 are added to 120 parts by weight of 75% ethanol solution, and ultrasonically dispersed for 30 minutes to obtain a dispersion;
[0047] S2.2: 14 parts by weight of nano titanium dioxide particles are added to the dispersion, and ultrasonically dispersed at 60° C. for 30 min. Subsequently, the mixture is centrifuged, washed with deionized water for 3 times, and dried at 75° C. for 8 h to obtain a composite hydrotalcite acid scavenger;
[0048] S3: Preparation of anti-PID composite fillers
[0049] S3.1: Add nano-tin oxide to deionized water, and ultrasonically disperse for 10 minutes to prepare a nano-tin oxide dispersion with a mass fraction of 5%. Add cetyltrimethylammonium bromide to the nano-tin oxide dispersion, and the amount of cetyltrimethylammonium bromide added is 3% of the mass of the nano-tin oxide dispersion. Stir magnetically for 40 minutes, and then ultrasonically disperse for 30 minutes. Then, filter, wash and dry to obtain surface-modified nano-tin oxide.
[0050] S3.2: Add barium metaphosphate to deionized water, ultrasonically disperse for 10 minutes to prepare a barium metaphosphate dispersion with a mass fraction of 5%, add silane coupling agent KH-550 to the barium metaphosphate dispersion, ultrasonically disperse for 40 minutes, and then add surface-modified nano-tin oxide, wherein the mixing mass ratio of surface-modified nano-tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion is 6:35:120, heat to 80°C, ultrasonically disperse for 90 minutes, and then, after centrifugation, washing and drying, obtain an anti-PID composite filler;
[0051] S4: Amination modification of anti-PID composite fillers
[0052] S4.1: Add 12 parts by weight of the anti-PID composite filler to 160 parts by weight of N,N-dimethylformamide, stir evenly, then add 45 parts by weight of ethylenediamine and 16 parts by weight of 30% ammonia water, stir and mix for 60 minutes, then continue stirring in a 60°C water bath for 40 minutes, then use a reflux condenser to condense and reflux for 6 hours, and filter the mixed solution obtained after condensation and reflux to obtain the filter residue;
[0053] S4.2: The filter residue is washed with anhydrous ethanol for 5 times to remove excess ethylenediamine, and the product obtained after washing is dried at 60° C. for 12 h to obtain an amino-anti-PID composite filler;
[0054] S5: Preparation of EVA film for acid-removing solar cells
[0055] 95 parts of EVA resin with a VA content of 28% and a melt index of 25 g / 10 min, 4 parts of tert-butyl peroxyacetate, 0.5 parts of triallyl isocyanurate, 3.2 parts of amino anti-PID composite fillers, 1.8 parts of composite hydrotalcite acid scavenger, 1.5 parts of stearamide, 1 part of 2,4-dihydroxybenzophenone, 1 part of bis-2,2,6,6-tetramethylpiperidinol sebacate, 1 part of antioxidant 1010 and 0.5 parts of silane coupling agent KH-550 are added into an extruder for melt blending to obtain a mixture. Subsequently, the mixture is extruded, cast, cooled and formed, and rolled to obtain an acid-removing EVA film for solar cells.
[0056] Example 2
[0057] A method for preparing an EVA film for an acid-removing solar cell, such as Figure 1 As shown, the specific steps include:
[0058] S1: Preparation of phosphate intercalated magnesium aluminum hydrotalcite
[0059] S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate into deionized water, stir and dissolve to form Mg 2+ The concentration is 2mol / L, Al 3+ Solution A with a concentration of 1 mol / L, add sodium hydroxide to deionized water, stir to dissolve, and prepare OH - Solution B with a concentration of 4 mol / L, add sodium phosphate to deionized water, stir and dissolve to prepare PO4 3- Solution C with a concentration of 1 mol / L;
[0060] S1.2: Pour solution C into the reactor, and slowly add solution A and solution B into the reactor while stirring under a nitrogen atmosphere. The dropping speed of solution A and solution B is 2 mL / min. When the volume ratio of the dropped solution A and solution B to the solution C in the reactor is 1:1:1, the dropping operation is completed. Stir the reaction for 1 hour, adjust the pH value of the mixed solution in the reactor to 7 with a sodium hydroxide solution with a concentration of 1 mol / L, and react at 70°C for 48 hours;
[0061] S1.3: After the treatment is completed and the mixture is cooled naturally, the obtained colloid is collected, washed with deionized water for 5 times, and then dried at 40° C. for 24 h to obtain phosphate-intercalated magnesium-aluminum hydrotalcite;
[0062] S2: Preparation of composite hydrotalcite acid scavenger
[0063] S2.1: 20 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 30 parts by weight of silane coupling agent KH-550 are added to 120 parts by weight of 75% ethanol solution, and ultrasonically dispersed for 20 minutes to obtain a dispersion;
[0064] S2.2: 14 parts by weight of nano titanium dioxide particles are added to the dispersion, and ultrasonically dispersed at 40° C. for 20 min. Subsequently, the mixture is centrifuged, washed with deionized water for 3 times, and dried at 80° C. for 4 h to obtain a composite hydrotalcite acid scavenger;
[0065] S3: Preparation of anti-PID composite fillers
[0066] S3.1: Add nano-tin oxide to deionized water, and ultrasonically disperse for 5 minutes to prepare a nano-tin oxide dispersion with a mass fraction of 5%. Add cetyltrimethylammonium bromide to the nano-tin oxide dispersion, and the amount of cetyltrimethylammonium bromide added is 3% of the mass of the nano-tin oxide dispersion. Stir magnetically for 20 minutes, and then ultrasonically disperse for 20 minutes. Then, filter, wash and dry to obtain surface-modified nano-tin oxide.
[0067] S3.2: Add barium metaphosphate to deionized water, ultrasonically disperse for 5 minutes to prepare a barium metaphosphate dispersion with a mass fraction of 5%, add silane coupling agent KH-550 to the barium metaphosphate dispersion, ultrasonically disperse for 20 minutes, and then add surface-modified nano-tin oxide, wherein the mixing mass ratio of surface-modified nano-tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion is 6:35:120, heat to 60°C, ultrasonically disperse for 60 minutes, and then, after centrifugation, washing and drying, obtain an anti-PID composite filler;
[0068] S4: Amination modification of anti-PID composite fillers
[0069] S4.1: Add 12 parts by weight of the anti-PID composite filler to 160 parts by weight of N,N-dimethylformamide, stir evenly, then add 45 parts by weight of ethylenediamine and 16 parts by weight of 30% ammonia water, stir and mix for 40 minutes, then continue stirring in a 45°C water bath for 40 minutes, then use a reflux condenser to condense and reflux for 4 hours, and filter the mixed solution obtained after condensation and reflux to obtain the filter residue;
[0070] S4.2: The filter residue is washed with anhydrous ethanol for 5 times to remove excess ethylenediamine, and the product obtained after washing is dried at 50° C. for 10 h to obtain an amino-anti-PID composite filler;
[0071] S5: Preparation of EVA film for acid-removing solar cells
[0072] 95 parts of EVA resin with a VA content of 28% and a melt index of 25 g / 10 min, 4 parts of tert-butyl peroxyacetate, 0.5 parts of triallyl isocyanurate, 3.2 parts of amino anti-PID composite fillers, 1.8 parts of composite hydrotalcite acid scavenger, 1.5 parts of stearamide, 1 part of 2,4-dihydroxybenzophenone, 1 part of bis-2,2,6,6-tetramethylpiperidinol sebacate, 1 part of antioxidant 1010 and 0.5 parts of silane coupling agent KH-550 are added into an extruder for melt blending to obtain a mixture. Subsequently, the mixture is extruded, cast, cooled and formed, and rolled to obtain an acid-removing EVA film for solar cells.
[0073] Example 3
[0074] A method for preparing an EVA film for an acid-removing solar cell, such as Figure 1 As shown, the specific steps include:
[0075] S1: Preparation of phosphate intercalated magnesium aluminum hydrotalcite
[0076] S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate into deionized water, stir and dissolve to form Mg 2+ The concentration is 2mol / L, Al 3+ Solution A with a concentration of 1 mol / L, add sodium hydroxide to deionized water, stir to dissolve, and prepare OH - Solution B with a concentration of 4 mol / L, add sodium phosphate to deionized water, stir and dissolve to prepare PO4 3- Solution C with a concentration of 0.5 mol / L;
[0077] S1.2: Pour solution C into the reactor, and slowly add solution A and solution B into the reactor while stirring under a nitrogen atmosphere. The dropping speed of solution A and solution B is 2 mL / min. When the volume ratio of the dropped solution A and solution B to the solution C in the reactor is 1.2:1:1, the dropping operation is completed. Stir the reaction for 2 h, adjust the pH value of the mixed solution in the reactor to 7 with a sodium hydroxide solution with a concentration of 1 mol / L, and react at 80°C for 24 h;
[0078] S1.3: After the treatment is completed and the mixture is cooled naturally, the obtained colloid is collected, washed with deionized water for 5 times, and then dried at 50° C. for 24 h to obtain phosphate-intercalated magnesium-aluminum hydrotalcite;
[0079] S2: Preparation of composite hydrotalcite acid scavenger
[0080] S2.1: 5 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 10 parts by weight of silane coupling agent KH-550 are added to 70 parts by weight of 75% ethanol solution, and ultrasonically dispersed for 30 minutes to obtain a dispersion;
[0081] S2.2: 2 parts by weight of nano titanium dioxide particles are added to the dispersion, and ultrasonically dispersed at 60° C. for 30 min. Subsequently, the mixture is centrifuged, washed with deionized water for 3 times, and dried at 75° C. for 8 h to obtain a composite hydrotalcite acid scavenger;
[0082] S3: Preparation of anti-PID composite fillers
[0083] S3.1: Add nano-tin oxide to deionized water, and ultrasonically disperse for 10 minutes to prepare a nano-tin oxide dispersion with a mass fraction of 3%. Add cetyltrimethylammonium bromide to the nano-tin oxide dispersion, and the amount of cetyltrimethylammonium bromide added is 3% of the mass of the nano-tin oxide dispersion. Stir magnetically for 40 minutes, and then ultrasonically disperse for 30 minutes. Then, filter, wash and dry to obtain surface-modified nano-tin oxide.
[0084] S3.2: Add barium metaphosphate to deionized water, ultrasonically disperse for 10 minutes to prepare a barium metaphosphate dispersion with a mass fraction of 8%, add silane coupling agent KH-550 to the barium metaphosphate dispersion, ultrasonically disperse for 40 minutes, and then add surface-modified nano-tin oxide, wherein the mixing mass ratio of surface-modified nano-tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion is 4:25:100, heat to 80°C, ultrasonically disperse for 90 minutes, and then, after centrifugation, washing and drying, obtain an anti-PID composite filler;
[0085] S4: Amination modification of anti-PID composite fillers
[0086] S4.1: Add 5 parts by weight of the anti-PID composite filler to 100 parts by weight of N,N-dimethylformamide, stir evenly, then add 30 parts by weight of ethylenediamine and 10 parts by weight of 30% ammonia water, stir and mix for 60 minutes, then continue stirring in a 60°C water bath for 40 minutes, then use a reflux condenser to condense and reflux for 6 hours, and filter the mixed solution obtained after condensation and reflux to obtain the filter residue;
[0087] S4.2: The filter residue is washed with anhydrous ethanol for 5 times to remove excess ethylenediamine, and the product obtained after washing is dried at 60° C. for 12 h to obtain an amino-anti-PID composite filler;
[0088] S5: Preparation of EVA film for acid-removing solar cells
[0089] 95 parts of EVA resin with a VA content of 28% and a melt index of 25 g / 10 min, 4 parts of tert-butyl peroxyacetate, 0.5 parts of triallyl isocyanurate, 3.2 parts of amino anti-PID composite fillers, 1.8 parts of composite hydrotalcite acid scavenger, 1.5 parts of stearamide, 1 part of 2,4-dihydroxybenzophenone, 1 part of bis-2,2,6,6-tetramethylpiperidinol sebacate, 1 part of antioxidant 1010 and 0.5 parts of silane coupling agent KH-550 are added into an extruder for melt blending to obtain a mixture. Subsequently, the mixture is extruded, cast, cooled and formed, and rolled to obtain an acid-removing EVA film for solar cells.
[0090] Comparative Example 1
[0091] Compared with Example 1, the difference of Comparative Example 1 is that step S2 is removed, and the composite hydrotalcite acid scavenger in step S5 is replaced by an equal weight portion of phosphate intercalated magnesium aluminum hydrotalcite obtained in step S1.3, and the other steps remain unchanged to prepare an acid-removing EVA film for solar cells, which is recorded as Comparative Example 1.
[0092] Comparative Example 2
[0093] Compared with Example 1, the difference of Comparative Example 2 is that the sodium phosphate in step S1.1 is replaced with sodium carbonate, and the sodium carbonate is added to deionized water, stirred and dissolved, and configured to form CO3 2- Solution D has a concentration of 1 mol / L. Solution C in step S1.2 is replaced by solution D to prepare carbonate-intercalated magnesium aluminum hydrotalcite. The phosphate-intercalated magnesium aluminum hydrotalcite in step S2.1 is replaced by carbonate-intercalated magnesium aluminum hydrotalcite. The other steps remain unchanged to prepare an EVA film for acid-removing solar cells, which is recorded as Comparative Example 2.
[0094] Comparative Example 3
[0095] Compared with Example 1, the difference of Comparative Example 3 is that steps S1.2-S1.3 are removed, solution B in step S1.1 is poured into the reactor, and solution A is slowly added dropwise to the reactor while stirring under a nitrogen atmosphere. The dropping rate of solution A is 2 mL / min. When the volume ratio of the solution A added dropwise to the solution B in the reactor is 1:1, the dropping operation is completed, the reaction is stirred for 2 hours, and the pH value of the mixed solution in the reactor is adjusted to 7 with a sodium hydroxide solution having a concentration of 1 mol / L. The reaction is carried out at 80°C for 24 hours. After the treatment is completed and naturally cooled, the obtained colloid is collected, washed with deionized water 5 times, and then dried at 50°C for 24 hours to obtain nitrate-intercalated magnesium-aluminum hydrotalcite. The phosphate-intercalated magnesium-aluminum hydrotalcite in step S2.1 is replaced with nitrate-intercalated magnesium-aluminum hydrotalcite. The other steps remain unchanged to prepare an EVA film for acid-removing solar cells, which is recorded as Comparative Example 3.
[0096] Comparative Example 4
[0097] Compared with Example 1, the difference of Comparative Example 4 is that step S4 is removed, and the amino anti-PID composite filler in step S5 is replaced by an anti-PID composite filler obtained in step S3.2 in equal weight portion. The other steps remain unchanged to prepare an acid-removing EVA film for solar cells, which is recorded as Comparative Example 4.
[0098] Comparative Example 5
[0099] Compared with Example 1, the difference of Comparative Example 5 is that steps S3-S4 are removed, and the amino anti-PID composite filler in step S5 is replaced by an equal weight portion of a mixed filler composed of nano-tin oxide and barium metaphosphate in a mass ratio of 1:1, and the other steps remain unchanged to prepare an acid-removing EVA film for solar cells, which is recorded as Comparative Example 5.
[0100] Performance Test:
[0101] (1) Power attenuation performance: The acid-removing EVA films for solar cells in Examples 1-3 and Comparative Examples 1-5 were respectively assembled into photovoltaic modules with the same polycrystalline silicon cells, glass and backplane using the same process. The photovoltaic modules assembled with the acid-removing EVA films for solar cells in Examples 1-3 and Comparative Examples 1-5 were tested according to IECTS62804-1 "Test method for voltage-induced attenuation detection of photovoltaic modules". The test conditions were as follows: temperature was 85°C, relative humidity was 90%, and the test time was 240h. The power attenuation of the photovoltaic modules before and after the test was tested. The test results are shown in Table 1;
[0102] (2) Mechanical properties: The tensile strength and elongation at break of the acid-removing solar cell EVA films in Examples 1-3 and Comparative Examples 1-5 were tested in accordance with GB / T29848-2018. The test results are shown in Table 2;
[0103] (3) Resistance to damp heat aging: The acid-removing solar cell EVA films in Examples 1-3 and Comparative Examples 1-5 were subjected to damp heat aging tests. The test conditions were as follows: temperature was 85°C, relative humidity was 85%, and the test time was 1000 h. The peak area of the carbonyl group in the carboxyl group of the acid-removing solar cell EVA film before and after the test was detected using a Fourier transform infrared spectrometer, and the peak area ratio P of the carbonyl group in the carboxyl group before and after the test was calculated. The calculation formula of the ratio P is: P = After the test (1760 cm -1 :-C=O free acetic acid) / before experiment (1760cm -1:-C=O free acetic acid), thereby inferring the free acid inventory of the acid-removing EVA film for solar cells; the light transmittance of the acid-removing EVA film for solar cells before and after the test was measured according to GB / T29848-2018, and the light transmittance retention rate was calculated. The calculation formula for the light transmittance retention rate is: light transmittance retention rate = light transmittance after the test / light transmittance before the test * 100%; the yellowing index (△YI) before and after the test was measured according to GB2409. The test results are shown in Table 3.
[0104] Table 1 Power attenuation performance results of the acid-removing solar cell EVA film assembled into photovoltaic modules in the examples and comparative examples
[0105]
[0106] Table 2 Mechanical properties of the acid-removing EVA films for solar cells in the examples and comparative examples
[0107]
[0108] Table 3 Results of the wet heat aging resistance of the acid-removing EVA films for solar cells in the examples and comparative examples
[0109]
[0110] As can be seen from Table 1-2, after the power attenuation performance and mechanical properties are tested, the power attenuation rate of the photovoltaic modules assembled from the EVA films for acid-removing solar cells in Examples 1-3 is ≥2%, and the tensile strength and elongation at break of the EVA films for acid-removing solar cells in Examples 1-3 are also better than those of Comparative Examples 1-5, indicating that the addition of the composite hydrotalcite acid scavenger and the amino anti-PID composite filler can improve the anti-PID performance of the EVA film for acid-removing solar cells, and is also beneficial to improving the mechanical properties of the EVA film for acid-removing solar cells. Secondly, as shown in Table 3, after the wet heat aging test, the free acid content in the acid-removing EVA film for solar cells in Examples 1-3 is significantly less than that in Comparative Examples 1-3, and the test results of the transmittance retention rate and the yellowing index change are also better than those in Comparative Examples 1-3, indicating that the composite hydrotalcite acid scavenger has excellent adsorption performance for acetic acid and good aging resistance, while the free acid content results in the acid-removing EVA film for solar cells in Comparative Examples 4-5 are between those in Examples 1-3 and Comparative Examples 1-3, and the test results of the transmittance retention rate and the yellowing index change are worse than those in Examples 1-3, indicating that the amino anti-PID composite filler also has a certain acid removal function, which reduces the content of acetic acid in the acid-removing EVA film for solar cells, and is also beneficial to improve the aging resistance of the acid-removing EVA film for solar cells.
[0111] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the appended claims of the present invention. Parts not described in detail in this specification belong to the prior art known to those skilled in the art.
Claims
1. An acid-removing EVA film for solar cells, characterized in that: By weight, it includes the following raw materials: 86-95 parts of EVA resin, 1.8-4 parts of main cross-linking agent, 0.1-0.5 parts of auxiliary cross-linking agent, 1.3-3.2 parts of amino anti-PID composite filler, 0.1-1.8 parts of composite hydrotalcite acid scavenger, 0.1-1.5 parts of lubricant, 0.04-1 parts of ultraviolet absorber, 0.01-1 parts of light stabilizer, 0.1-1 parts of antioxidant and 0.1-0.5 parts of coupling agent; The raw materials for preparing the composite hydrotalcite acid scavenger include: 5 to 20 parts of phosphate intercalated magnesium aluminum hydrotalcite, 1 to 14 parts of nano titanium dioxide particles, 10 to 30 parts of silane coupling agent KH-550 and 70 to 120 parts of 75% by mass ethanol solution, wherein the phosphate intercalated magnesium aluminum hydrotalcite is a layered composite material formed by inserting phosphate ions between magnesium aluminum hydrotalcite layers; The raw materials for preparing the amination anti-PID composite filler include: 1 to 12 parts of the anti-PID composite filler, 100 to 160 parts of N, N-dimethylformamide, 20 to 45 parts of ethylenediamine and 6 to 16 parts of 30% ammonia water by mass; The raw materials for preparing the anti-PID composite filler include: surface-modified nano tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion, wherein the mixing mass ratio of the surface-modified nano tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion is (1-6): (21-35): (90-130), the surface-modified nano tin oxide is nano tin oxide modified by a surfactant, and the mass fraction of the barium metaphosphate dispersion is 4-8%.
2. The acid-removing solar cell EVA film according to claim 1, characterized in that: The VA content of EVA resin is 28-33%, and the melt index is 25-43 g / 10 min.
3. The acid-removing solar cell EVA film according to claim 2, characterized in that: The main cross-linking agent is at least one of tert-butyl peroxycarbonate-2-ethylhexyl, tert-amyl peroxy (2-ethylhexyl) carbonate, tert-butyl peroxyacetate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate or diisopropylbenzene peroxide; the auxiliary cross-linking agent is at least one of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated neopentyl glycol diacrylate, and ethoxylated trimethylolpropane triacrylate; the lubricant is one or more of stearic acid, calcium stearate, zinc stearate, butyl stearate, stearamide, and oleamide; the ultraviolet absorber is phenyl o-hydroxybenzoate, 2-(2'-hydroxy- The invention discloses a novel light stabilizer comprising at least one of bis-2,2,6,6-tetramethylpiperidinol sebacate, N,N,-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine and 2,4-dichloro-6-(4-morpholinyl)-1,3,5-triazine; a coupling agent comprising at least one of silane coupling agent KH-570, silane coupling agent KH-560, silane coupling agent KH-670 and silane coupling agent KH-550; and an antioxidant comprising at least one of antioxidant 1010 and antioxidant 168.
4. A method for preparing the acid-removing EVA film for solar cells according to claim 3, characterized in that: The steps include: S1: Preparation of phosphate intercalated magnesium aluminum hydrotalcite, using magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and phosphate as raw materials, sodium hydroxide as a precipitant, deionized water as a solvent, preparing a solution, titrating coprecipitation, hydrothermal treatment, washing and drying to obtain phosphate intercalated magnesium aluminum hydrotalcite; S2: Preparation of composite hydrotalcite acid scavenger: after dispersing and mixing phosphate intercalated magnesium aluminum hydrotalcite, silane coupling agent KH-550 and 75% ethanol solution by mass, nano-titanium dioxide particles were added, and the composite hydrotalcite acid scavenger was obtained after ultrasonic dispersion, centrifugal separation, washing and drying; S3: Preparation of anti-PID composite filler: surface modification of nano-tin oxide is performed using a surfactant to obtain surface-modified nano-tin oxide, and barium metaphosphate dispersion, silane coupling agent KH-550 and surface-modified nano-tin oxide are mixed and dispersed, and then centrifuged, washed and dried to obtain an anti-PID composite filler; S4: Amination modification of the anti-PID composite filler, wherein the anti-PID composite filler, N,N-dimethylformamide, ethylenediamine and 30% ammonia water are mixed, and the mixture is heated and stirred in a water bath, condensed and refluxed, filtered to obtain the residue, washed and dried to obtain the amination anti-PID composite filler; S5: Preparation of EVA film for acid-removing solar cells, EVA resin, main cross-linking agent, auxiliary cross-linking agent, amino anti-PID composite filler, composite hydrotalcite acid scavenger, lubricant, ultraviolet absorber, light stabilizer, antioxidant and coupling agent are melt-blended, and then extruded, cast, cooled and formed, and rolled up to obtain the EVA film for acid-removing solar cells.
5. The method for preparing the acid-removing solar cell EVA film according to claim 4, wherein: Step S1: Preparation of phosphate intercalated magnesium aluminum hydrotalcite, specifically comprising the following steps: S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate into deionized water, stir and dissolve to form Mg 2+ The concentration is 1.5~2.5mol / L, Al 3+ Solution A with a concentration of 0.5 to 1.5 mol / L, add sodium hydroxide to deionized water, stir to dissolve, and prepare OH - Solution B with a concentration of 1.5 to 4 mol / L, add phosphate to deionized water, stir to dissolve, and prepare PO4 3- Solution C with a concentration of 0.2 to 1 mol / L; S1.2: Pour solution C into the reactor, and slowly drop solution A and solution B into the reactor while stirring under a nitrogen atmosphere. The dropping speed of solution A and solution B is 2 mL / min. When the volume ratio of the dropped solution A and solution B to the solution C in the reactor is (1-1.2):1:1, the dropping operation is completed. Stir the reaction for 1-2 hours, adjust the pH value of the mixed solution in the reactor to 6-8 with a sodium hydroxide solution with a concentration of 1 mol / L, and react at 70-80°C for 12-48 hours; S1.3: After the treatment is completed and the mixture is cooled naturally, the obtained colloid is collected, washed with deionized water for 2 to 5 times, and then dried at 40 to 60° C. for 12 to 24 hours to obtain phosphate-intercalated magnesium aluminum hydrotalcite.
6. The method for preparing the acid-removing solar cell EVA film according to claim 5, wherein: In step S1.1, the phosphate is sodium phosphate or potassium phosphate.
7. The method for preparing the acid-removing solar cell EVA film according to claim 6, wherein: Step S2: Preparation of composite hydrotalcite acid scavenger, specifically comprising the following steps: S2.1: Add 5 to 20 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 10 to 30 parts by weight of silane coupling agent KH-550 to 70 to 120 parts by weight of 75% ethanol solution, and ultrasonically disperse for 20 to 30 minutes to obtain a dispersion; S2.2: Add 1 to 14 parts by weight of nano titanium dioxide particles to the dispersion, and ultrasonically disperse at 40 to 60° C. for 20 to 30 minutes. Subsequently, centrifuge and wash with deionized water for 2 to 3 times, and dry at 70 to 80° C. for 4 to 8 hours to obtain a composite hydrotalcite acid scavenger.
8. The method for preparing the acid-removing solar cell EVA film according to claim 7, wherein: Step S3: Preparation of anti-PID composite filler, specifically comprising the following steps: S3.1: Add nano-tin oxide to deionized water, ultrasonically disperse for 5 to 10 minutes, and prepare a nano-tin oxide dispersion with a mass fraction of 2 to 5%. Add a surfactant to the nano-tin oxide dispersion, wherein the amount of the surfactant added is 1 to 3% of the mass of the nano-tin oxide dispersion, and the surfactant is hexadecyltrimethylammonium bromide. Stir magnetically for 20 to 40 minutes, and then ultrasonically disperse for 10 to 30 minutes. Then, filter, wash and dry to obtain the surface-modified nano-tin oxide. S3.2: Add barium metaphosphate to deionized water and ultrasonically disperse for 5 to 10 minutes to prepare a barium metaphosphate dispersion with a mass fraction of 4 to 8%. Add silane coupling agent KH-550 to the barium metaphosphate dispersion and ultrasonically disperse for 20 to 40 minutes. Then, add the surface-modified nano-tin oxide, heat to 50 to 80°C, and ultrasonically disperse for 40 to 90 minutes. Then, after centrifugation, washing and drying, an anti-PID composite filler is obtained.
9. The method for preparing the acid-removing solar cell EVA film according to claim 8, wherein: In step S3.2, the mixing mass ratio of the surface-modified nano-tin oxide, the silane coupling agent KH-550 and the barium metaphosphate dispersion is (1-6): (21-35): (90-130).
10. The method for preparing the acid-removing EVA film for solar cells according to claim 9, characterized in that: Step S4: Amination modification of the anti-PID composite filler, specifically comprising the following steps: S4.1: Add 1 to 12 parts by weight of anti-PID composite filler to 100 to 160 parts by weight of N,N-dimethylformamide, stir evenly, then add 20 to 45 parts by weight of ethylenediamine and 6 to 16 parts by weight of 30% ammonia water, stir and mix for 40 to 60 minutes, then continue stirring in a 45 to 60°C water bath for 20 to 40 minutes, then use a reflux condenser to condense and reflux for 4 to 6 hours, and filter the mixed solution obtained after condensation and reflux to obtain the filter residue; S4.2: The filter residue is washed with anhydrous ethanol for 3 to 5 times to remove excess ethylenediamine, and the product obtained after washing is dried at 50 to 60° C. for 6 to 12 hours to obtain an amino-anti-PID composite filler.
Citation Information
Patent Citations
Deacidification type EVA packaging adhesive film and preparation method thereof
CN117866546A
Hydrolysis-resistant and PID-resistant EVA (Ethylene Vinyl Acetate) adhesive film for solar packaging material and preparation method thereof
CN118185503A